Meningkatkan Kemampuan Berfikir Kritis Pada Pembelajaran PAK Materi Peran Sekolah Bagi Perkembanganku Dengan Model PBL Berbantu PPT Bagi Siswa Kelas VII SMP Negeri 1 Tanjungpinang - Antonius Sugihartanto; Mawarni Gea; Agustinus Mulyono (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This classroom action research evaluates the effectiveness of Problem Based Learning (PBL) in improving critical thinking skills in Catholic Religious Education (PAK) learning in class VII of SMP Negeri 1 Tanjungpinang. Involving 13 students in two cycles, the research used quantitative and qualitative methods. The research results showed significant improvements in cognitive and affective aspects. The average cognitive score increased from 71 in the pre-cycle to 86.6 in the second cycle, with learning completeness reaching 100% from initially only 15.38%. The average affective score also increased from 74 in the first cycle to 84 in the second cycle. Observations indicated increased student engagement in discussions, reflecting development of critical thinking skills. This research concludes the effectiveness of PBL in improving critical thinking skills and PAK learning outcomes, recommending wider application and further research.